THE COMPARATIVE ANALYSIS OF PHRASAL VERBS IN UZBEK AND ENGLISH LANGUAGES (Ta'limning zamonaviy transformatsiyasi, 2024)
This article presents a comparative analysis of phrasal verbs in the Uzbek and English languages. The study examines the similarities and differences between these two languages in terms of the structure, usage, and meaning of phrasal verbs. The findings of this study contribute to our understanding of the cross-linguistic variations in phrasal verb usage and offer valuable implications for language teaching and learning.Эта статья представляет собой сравнительный анализ фразовых глаголов в узбекском и английском языках. Исследование рассматривает сходства и различия между этими двумя языками в терминах структуры, использования и значения фразовых глаголов. Полученные результаты исследования способствуют нашему пониманию межъязыковых вариаций в использовании фразовых глаголов и предлагают ценные рекомендации для преподавания и изучения языка.Ushbu maqola o'zbek va ingliz tillaridagi frasilalarni taqqoslashga oid taqsimot-tahlillarni taklif etadi. O'zbek va ingliz tillari frasilalarining tuzilishi, foydalanishi va ma'nosi bo'yicha bu ikkita tilda o'rtacha xossalarni o'rganishga oid taqsimot-tahlillar ko'radiUshbu tadqiqot natijalari frasilalarni tashqi-tiliy o'zgarishlar bo'yicha tushuntirishimizga xizmat qiladi va til o'rganish va o'qitish uchun muhim tavsiyalar taklif qiladi.